Substituição da farinha de peixe por fontes alternativas de proteína animal no cultivo de alevinos de peixe-rei (Odontesthes bonariensis). - Portelinha, Mauro Kaster (2011)
Peixe-rei fish of the gender Odontesthes are native in southern Brazil, being an important income source for regional handicraft fishing and has been object of studies for utilization in intensive cultivation. Studies show that fingerlings production are feasible and recommend diets with crude protein levels between 45 and 50%, with 30% of total protein should be originated from fish meal. The objective of this study was to evaluate the performance of peixe-rei fingerlings, fed with other sources of animal protein, in substitution of fish meal, allowing new alternatives in the formulation and development of diets for regional fish species. The experiment was conducted in the Ictiology Laboratory, Animal Science Department, Faculty of Agronomy Eliseu Maciel. Experimental units were consisted of 39 water tanks with capacity of 50 liters each. Each aquarium received five peixe-rei fingerlings, measuring 8.02 +/- 0.28 cm of total length and average weight of 3,30 +/- 0,58 g. Environment variables as temperature, dissolved oxygen, pH, alkalinity and total ammonia did not show significant variations. Experimental diets were formulated using the software Super Crac, containing a minimum of 30% of aninal meal (fish, earth worms, chicken guts or bovine blood). The rate of feeding was of 5% of biomass/day. Experimental design was entirely randomized, with twelve (12) treatments and three replications, where fish meal was replaced by bovine blood meal, chiken guts meal and earth worm meal at levels of 25, 50, 75 and 100% and compared to a control treatment, where the only source of animal protein was fish meal. Results of weight gain show that chicken guts meal is a good substitute for fish meal in the diest of peixe-rei; the use 56% of gut meal and 44% of fish meal presented the highest weigth gain. Blood meal substitutes satisfactorily the fish meal up to a level of 50%. Earth worm meal included as substitute of fish meal up to level of 19.7% favored the weight gain of animals. The results show the feasibility of partial replacementof fish meal by alternative sources of animal protein originating from animal residues, in the diet of peixe-rei.